Liverwurst is missing - Mayer, Mercer, 1943- (Four Winds Press, 1981)
When Liverwurst the baby rhinosterwurst disappears, Wackatoo Indians, survivors of the 49th Cavalry, and children from the Koala Scouts join the circus company in rescuing him from a burger tycoon interested in creating Rhino-burgers.